PENGARUH KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA DINAS PERPUSTAKAAN DAN KEARSIPAN PROVINSI SULAWESI SELATAN - Edy Jumady; Dharmawati Djaharuddin; Ampauleng Ampauleng; A. Dahrul; Kusdiningsih M. Torano (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2022)
This study aims to examine and analyze the influence of leadership and work motivation on the performance of the employees of the Library and Archives Service of South Sulawesi Province. The research questions posed in this study are: (1) whether leadership affects employee performance, (2) whether work motivation affects employee performance, (3) whether leadership and motivation simultaneously affect employee performance at the Sulawesi Provincial Library and Archives Service. South. This research was conducted at the Library and Archives Service company of South Sulawesi Province. The sampling technique used was the determination of the sample size based on purposive sampling using the Slovin formula with a total sample of 65 respondents. The method of data analysis in this study is multiple regression analysis. The study found that the hypothesis in this study has been significantly proven. (1) leadership (X1) partially has a positive and significant effect on employee performance. (2) work motivation (X2) partially has a positive and insignificant effect on employee performance, leadership (X1) and work motivation (X2) simultaneously affect the performance of employee at Library and Archives Service of South Sulawesi Province.